Role of Cognitive Behavioral Therapy in Treating Depression among Adults in South Korea - Hana, Lim (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the role of cognitive behavioral therapy in treating depression among adults in South Korea. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Cognitive Behavioral Therapy (CBT) has proven to be an effective approach for treating depression among adults in South Korea, showing significant improvements in symptom reduction and mental well-being. It helps individuals identify and change negative thought patterns, enhancing emotional regulation and coping skills. Clinical findings reveal that CBT leads to substantial decreases in depressive symptoms compared to traditional care. Its structured and goal-oriented nature aligns well with South Korea’s emphasis on practical, evidence-based mental health interventions. Unique Contribution to Theory, Practice and Policy: Cognitive theory of depression, behavioral activation theory & biopsychosocial model may be used to anchor future studies on the role of cognitive behavioral therapy in treating depression among adults in South Korea. Clinicians should continue to integrate CBT as a first-line treatment for depression, emphasizing its role in both reducing symptoms and improving long-term emotional resilience. Policymakers should consider expanding access to CBT, particularly in public health systems, due to its cost-effectiveness and proven success in treating depression.